2006
DOI: 10.1093/brain/awl061
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in mitochondrial myopathies is linked to mitochondrial proliferation

Abstract: Increased susceptibility to apoptosis has been shown in many models of mitochondrial defects but its relevance to human diseases is still discussed. We addressed the presence of apoptosis in muscle from patients with mitochondrial DNA (mtDNA) disorders. Taking advantage of the mosaic pattern of muscle morphological anomalies associated with heteroplasmic mtDNA alterations, we have used an in situ approach to address the relationship between apoptosis and respiratory defect, mitochondrial proliferation and muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 38 publications
4
61
0
Order By: Relevance
“…Previous studies have shown mitochondrial defects associated with the development of myopathies [16,17]. The results presented here agree with those that link apoptosis with higher mutation rate in mitochondrial genes and an increased mitochondrial mass in human myopathies that are associated with intolerance to exercise, defects in the energy production and muscle weakness [18].…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have shown mitochondrial defects associated with the development of myopathies [16,17]. The results presented here agree with those that link apoptosis with higher mutation rate in mitochondrial genes and an increased mitochondrial mass in human myopathies that are associated with intolerance to exercise, defects in the energy production and muscle weakness [18].…”
Section: Resultssupporting
confidence: 91%
“…Despite the preservation of the levels of COX activity, the altered ratio between MT-CO2p and COX4p implied that some COX complexes had an abnormal composition, thus provoking focal respiratory defects. In addition, mitochondrial proliferation has been demonstrated to be an essential factor for the induction of apoptosis in mitochondrial myopathy (1). The amount of the activated form of caspase 3, a hallmark of the cellular commitment to apoptosis (8), was therefore assessed with ELISA and found to be significantly increased in the patients' samples (median, 156% of control value, versus 110% in control samples; P ϭ 0.02) (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Despite global compensation at the tissue level, altered mitochondrial composition and increased mitochondrial mass were associated with mitochondrion-borne deleterious mechanisms, such as oxidative stress and apoptosis (1). Indeed, the expression of DDIT3, a transcription factor induced by mitochondrial reactive oxygen species (6), was increased in patients' samples.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, many researchers tried to clarify the correlation between apoptosis-related cell death and pathogenic mechanism involved in the defects in muscle and brain of patients with mitochondrial encephalomyopathies. Many well-documented studies have revealed that apoptosis is involved in the progression of muscle myopathy (Aure et al, 2006;Umaki et al, 2002). Studies showed significant signs of apoptosis in the COX-negative muscle fibers in muscle biopsies from patients who harbored high proportions of specific point mutations in tRNA genes of mtDNA.…”
Section: Mitochondrial Dysfunction-induced Cell Death and Mitochondrimentioning
confidence: 99%